Selection of Bacillus thuringiensis strains toxic to Meloidogyne incognita - Jônatas Barros dos Santos; Alberto do Nascimento Silva; Paulo Roberto Martins Queiroz; Barbara Eckstein; Rose Gomes Monnerat (Pesquisa Agropecuária Tropical, 2022)
The Bacillus thuringiensis bacterium has demonstrated an effective potential in the control of several agricultural pests, among them nematodes.This study aimed to standardize and establish a methodology of bioassays of B. thuringiensisand Meloidogyne incognita with the use of resorcinol, select B. thuringiensis strains toxic to M. incognitain vitroand molecularly identify the presence of the cry6 gene in B. thuringiensis strains. Second-stage juveniles were subjected to resorcinol doses, verifying that the concentration of 0.2 % did not cause mortality and provided the Cry6A toxin ingestion. Thereafter, 16 B. thuringiensis strains were tested in the presence or absence of resorcinol, resulting in mortality rates of 4-36 %. Among the B. thuringiensis strains analyzed for the presence of the cry6 gene, only one was detected (S1617).